Optimasi Proses Deployment dengan Blue-Green Deployment Berbasis Containerization untuk Mencapai Zero Downtime - Ramadhan, Restu Bumi Ryan; Hadi, Abdul; Maryamah, Siti (STMIK Palangkaraya, 2025)
Downtime during deployment remains a major challenge that can disrupt service availability and reduce user trust in websites. This study aims to implement and evaluate the effectiveness of a blue-green deployment strategy based on containerization to achieve zero downtime. The implementation utilizes Docker and Traefik on an infrastructure of separate Virtual Private Servers for frontend and backend services, automated through a CI/CD pipeline using GitHub Actions. The evaluation compares non-Blue-Green and Blue-Green deployment scenarios based on operational indicators such as downtime duration, service stability, and rollback capability in case of failures. The results show that the Blue-Green strategy successfully reduces downtime from an average of 80 seconds in the non-Blue-Green scenario to zero seconds, accelerates rollback processes, and improves system scalability. Although the configuration becomes more complex, this approach proves to be safe, reliable, and effective in supporting continuous deployment in modern DevOps practices that demand uninterrupted services